Interspeech 2020 2020
DOI: 10.21437/interspeech.2020-2253
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Discrimination of Apraxia of Speech and Dysarthria Using a Minimalistic Set of Handcrafted Features

Abstract: To assist clinicians in the differential diagnosis and treatment of motor speech disorders, it is imperative to establish objective tools which can reliably characterize different subtypes of disorders such as apraxia of speech (AoS) and dysarthria. Objective tools in the context of speech disorders typically rely on thousands of acoustic features, which raises the risk of difficulties in the interpretation of the underlying mechanisms, overadaptation to training data, and weak generalization capabilities to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The acoustic features proposed in this paper for discriminating between dysarthria, AoS, and neurotypical speech are motivated by the advantageous performance these features have shown in discriminating between dysarthria and neurotypical speech in [16] and in discriminating between dysarthria and AoS in [17]. In the following, a brief overview of these features is presented.…”
Section: Acoustic Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…The acoustic features proposed in this paper for discriminating between dysarthria, AoS, and neurotypical speech are motivated by the advantageous performance these features have shown in discriminating between dysarthria and neurotypical speech in [16] and in discriminating between dysarthria and AoS in [17]. In the following, a brief overview of these features is presented.…”
Section: Acoustic Featuresmentioning
confidence: 99%
“…In [16], we have shown that spectral sparsity can successfully characterize imprecise articulation, abnormal pauses, and breathiness observed in dysarthria. Spectral sparsity describes the energy distribution of the speech spectral coefficients across time and is computed by i) transforming the signals to the short-time Fourier transform domain, ii) time-aligning all representations to a 1 For additional details on the motivation behind these features and their computation, the interested reader is referred to [16,17]. reference representation, and iii) computing the shape parameter of a Chi distribution best modeling the spectral magnitudes in each time frame [16].…”
Section: Acoustic Featuresmentioning
confidence: 99%
See 3 more Smart Citations